TANGGUNG JAWAB REKANAN PEMERINTAH DALAM PELAKSANAAN PROYEK PEMBANGUNAN JEMBATAN KEMBAR DI KOTA SAMARINDA BERDASARKAN PERATURAN GUBERNUR KALIMANTAN TIMUR NOMOR 38 TAHUN 2012 - Rinto Rinto (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT Mahakam’s bridge was a bridge that connected Samarinda with Samarinda Seberang and other cities like Balikpapan, Kukar and Kubar. Along with the rapid of population growth and economic in Samarinda gave an impact to the user of traffic to the bridge over the Mahakam that connected Samarinda’s city and Samarinda Seberang with the inter-city and other areas. As the reality that happened in Samarinda, in the afternoon and holidays the traffic to Mahakam’s bridge and otherwise always jammed with vehicle till made a severe traffic jammed in the second pathway of Mahakam’s bridge. According to the problems above, the government of Kalimantan Timur took a wise solution with made an initiative to build a same bridge in the left of Mahakam bridges. With the construction of the twin bridges, the writers interested to know how the responsibility of the government partners in the construction of the twin bridges. This research method that used in this law script is descriptive design where the writer described the reality of the twin bridges construction and customized with data from Dinas Pekerjaan Umum Bidang Bina Marga Kementerian Pekerjaan Umum. . The legal standings that used in construction of the twins bridges in Samarinda is the governor rule of Kalimantan Timur Nomor 38 Tahun 2012, from the governor rule of Kalimantan Timur all the rules that became the legal standings in construction of the twins bridges so have a legally enforceable. Based on the condition of twin’s bridges construction today, the process of building Twins Bridge is foundation construction stage. The foundation of Twins Bridge could be seen by the people when they passed through the twin bridge. After the writer conducted research in Dinas Pekerjaan Umum Bidang Bina Marga Kementerian Pekerjaan Umum the writer concluded that the responsibility of government partner in twins bridge construction based on the contract between the government of Kalimantan Timur with the government partners is the Contractor, PT. PP Perdana KSO, Consultant Planner is PT. Perencana Jaya and the supervising consultants is PT. Pelaksana Desain Karya Cipta. Keywords : (The Twins Bridge)